EPID-11. A POPULATION STUDY OF CLINICAL TRIAL ACCRUAL FOR WOMEN AND MINORITIES IN NEURO-ONCOLOGY FOLLOWING THE NIH REVITALIZATION ACT. (12th November 2021) - Reihl, Sheantel; Patil, Nirav; Morshed, Ramin; Mehari, Mulki; Aabedi, alexander; Chukwueke, Ugonma; Porter, Alyx; Fontil, Valy; Cioffi, Gino; Waite, Kristin; Kruchko, Carol; Ostrom, Quinn; et al.
Abstract: INTRODUCTION: The NIH Revitalization Act, implemented 29 years ago, set to improve the representation of women and minorities in clinical trials. In this study, we investigate the progress made in neuro-oncology in all phase therapeutic clinical trials for neuro-epithelial central nervous system tumors in comparison to their demographic-specific age-adjusted disease incidence and mortality. METHODS: Registry study of all published clinical trials for World Health Organization (WHO) defined neuro-epithelial CNS tumors between January 2000 and December 2019. Study participants for trials were obtained from PubMed and ClinicalTrials.gov. Population-based data from the CBTRUS for incidence analyses. SEER-18 Incidence-Based Mortality data was used for mortality analysis. Descriptive statistics, Fisher exact, and c 2 tests were used to analyze the data. RESULTS: Among 662 published clinical trial articles representing 49, 907 accrued participants, 62.5% of study participants were men and 37.5% were women (P< 0.0001) representing a mortality specific over-accrual for men (P= 0.001) and under-accrual for women (P= 0.001). Whites, Asians, Blacks, and Hispanics represented 91.7%, 1.5%, 2.6%, and 1.7% of trial participants. Compared with their US cancer mortality, Blacks (47% of expected mortality, P=.008), Hispanics (17% of expected mortality, P< .001) and Asians (33% of expected mortality, P< .001) were underrepresented compared with Whites (114% of expected mortality, P< .001). CONCLUSIONS: Nearly 30 years since the Revitalization Act, minorities and women are consistently underrepresented when compared with their demographic-specific incidence and mortality in therapeutic clinical trials for neuroepithelial tumors. This study provides a framework for investigating cancer clinical trial accrual and offers guidance regarding workforce factors associated with enrollment of vulnerable patients.